Inclusive education in learning accompaniment alternatives - Gorozabel Quiñonez, Josefa Elizabeth; Calle García, Robertson Xavier; Rodríguez Gámez, María (International Journal of Psychosocial Rehabilitation, 2020)
Inclusive education constitutes an educational approach, which has its foundations in the valuation of diversity, as an enriching element of the teaching-learning process and conducive to human development. To achieve the quality of this type of teaching, it is necessary to raise the level of teacher training, carry out regular training and have good support, gradually contributing to the safe development of the social and academic environment in all children in the classroom and thus avoid possible errors that teachers can commit due to the lack of knowledge in these situations. This article aims to address the interrelationship between inclusive education, pedagogical support, the quality of teaching and with learning. The applied methodology was hermeneutical research, in which the inputs of the thematic literature and their possible inferential analysis were described. The result was that inclusive education is the best option for children with special needs and the importance of teacher training, as well as the constant evaluation of the teaching process.